Swimming against the tide of opinion self-esteem built to last - Porras, Jerry I. (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from Success built to last: creating a life that matters (ISBN: 9780132287517) by Jerry Porras, Stewart Emery, and Mark Thompson. Try, fail, try again, win small, win a bit bigger, dig deeper inside ... and do more than you ever imagined you could!"--Resource description page.